Advances in H-mode physics for long-pulse operation on EAST. (29th July 2015) - Wan, Baonian; Li, Jiangang; Guo, Houyang; Liang, Yunfeng; Xu, Guosheng; Wang, Liang; Gong, Xianzu
Abstract: Since the 2012 International Atomic Energy Agency Fusion Energy Conference (IAEA-FEC), significant advances in both physics and technology has been made on the Experimental Advanced Superconducting Tomakak (EAST) toward a long-pulse stable high-confinement (H-mode) plasma regime. The experimental capabilities of EAST have been technically upgraded with the power enhancement (source power up to 26 MW) of the continuous-wave heating and current drive system, replacement of the upper graphite divertor with an ITER-like W monoblock divertor, and installation of a new internal cryopump in the upper divertor and a set of 16 in-vessel resonant magnetic perturbation (RMP) coils. This new upgrade enables EAST to be a unique operating device capable of investigating ITER-relevant long-pulse high-performance operations with dominant electron heating and low torque input within the next 5 years. Remarkable physics progress in controlling transient and steady-state divertor heat fluxes has been achieved on EAST, e.g. (i) edge-localized mode (ELM) mitigation/suppression with a number of attractive methods including lower hybrid wave (LHW), supersonic molecular beam injection (SMBI), RMPs, and real-time Li aerosol injection; and (ii) active control of steady-state power distribution by the synergy of LHW and SMBI. In the 2014 experimental campaign, a long-pulse high-performance H-mode plasma with H98 ∼ 1.2 has been obtained with a duration over 28 s (∼200 times the energy confinement time). In addition, several new experimental advances have been achieved in the last EAST campaign, including: (i) high-performance H-mode with β N ∼ 2 and stored plasma energy ∼220 kJ; (ii) H-mode plasma sustained by neutral beam injection (NBI) alone or modulated NBI with lower hybrid current drive (LHCD), for the first time in EAST; (iii) high current drive efficiency and nearly full noninductive plasmas maintained by the new 4.6 GHz LHCD system; (iv) demonstration of a quasi-snowflake divertor configuration; and (v) observation of a new edge-coherent mode and its effects on edge transport in H-mode plasmas.